Electronic palliative care coordinating systems (EPaCCS) may not facilitate home deaths: A mixed methods evaluation of end of life care in two English counties. (March 2016) - Wye, Lesley; Lasseter, Gemma; Simmonds, Bethany; Duncan, Lorna; Percival, John; Purdy, Sarah
Electronic palliative care coordination systems (EPaCCS) detail preferred place of death across health and voluntary sector boundaries. Quantitative studies suggest that individuals recorded on EPaCCS are more likely to die at home. This study aimed to explore this relationship between EPaCCS and home deaths. Patient records from EPaCCS were collected from 1 September 2011 to 29 February 2012, linked to death data and analysed using descriptive statistics. We interviewed 101 professionals, including community nurses, and employed framework analysis. Few eligible patients were entered on EPaCCS (9% North Somerset, 13% Somerset). Of those, the majority died in community settings (87%, 81/93 North Somerset; 93% 307/331 Somerset). However, interviews and EPaCCS record analysis suggested that EPaCCS was almost exclusively used by community nurses and GPs, so, unsurprisingly, the relationship between EPaCCS and home deaths was strong. Difficulties included professional reluctance to discuss death, and the burden of data entry falling on daytime staff for out-of-hours colleagues. These results challenge assumptions that EPaCCS facilitates increased home deaths, as qualitative investigation identified selection bias. To avoid misinterpretations, future studies should employ mixed methods. The implementation of an electronic tool is not enough on its own to ensure that advanced care wishes are available, as long-standing organisational and cultural issues, such as professionals working in silos and professional reluctance to have 'end of life' discussions, also need to be addressed.